When the Sound Becomes the Goal. 4E Cognition and Teleomusicality in Early Infancy - Schiavio, Andrea; van der Schyff, Dylan; Kruse-Weber, Silke; Timmers, Renee (Frontiers in Psychology, 2017)
In this paper we explore early musical behaviours through the lenses of the recently emerged ‘4E’ approach to mind, which sees cognitive processes as Embodied, Embedded, Enacted, and Extended. In doing so, we draw from a range of interdisciplinary theoretical and empirical research, engaging in critical and constructive discussions with both new findings and existing positions. In particular, we refer to observational research by French pedagogue and psychologist François Delalande, who examined infants’ first ‘sound discoveries’ and individuated three different musical ‘conducts’ inspired by the ‘phases of the game’ originally postulated by Piaget. Elaborating on such ideas we introduce the notion of ‘teleomusicality’, which describes the goal-directed behaviours infants adopt to explore and play with sounds. This is distinguished from the developmentally earlier ‘protomusicality’, which is based on music-like utterances, movements, and emotionally relevant interactions (e.g., with primary caregivers) that do not entail a primary focus on sound itself. Such distinction - which involves an ‘attentive shift’ occurring between 6 and 10 months of age - helps develop a conceptual framework for early musical development that emphasises the emergence of exploratory, goal-directed (i.e., sound-oriented), and self-organized, musical actions in infancy. In line with this, we provide a preliminary taxonomy of teleomusical processes discussing ‘Original Teleomusical Acts’ (OTAs) and ‘Constituted Teleomusical Acts’ (CTAs). We argue that while OTAs can be easily witnessed in infants’ exploratory behaviours, CTAs involve the mastery of more specific and complex goal-directed chains of actions central to musical activity.